The effect of peer observation on consumption choices: experimental evidence - Sahra Sakha; Antonia Grohmann (Deutsche Bundesbank, 2016)
This paper investigates the impact of peer observation on the consumption decisions of rural households in Thailand using a lab-in-the-field experiment. We find that those groups that observe each other show lower within group standard deviation in their decisions. Thus, we find evidence for conformity. Further, we find that individual's consumption choice is influenced by the group choice controlling for large number of individual, household, and village characteristics. We find that unfamiliarity of the product is counteracted by peer effects. Finally, we find evidence of treatment heterogeneity with regards to cognitive ability and village size.
Keywords: D12; C21; C92; 330; Consumption; Peer Effects; Conformity